Phonological working memory and FOXP2 - Schulze, Katrin; Vargha-Khadem, Faraneh; Mishkin, Mortimer (Neuropsychologia, 2018)
The discovery and description of the affected members of the KE family (aKE) initiated research on how genes enable the unique human trait of speech and language. Many aspects of this genetic influence on speech-related cognitive mechanisms are still elusive, e.g. if and how cognitive processes not directly involved in speech production are affected. In the current study we investigated the effect of the FOXP2 mutation on Working Memory (WM). Half the members of the multigenerational KE family have an inherited speech-language disorder, characterised as a verbal and orofacial dyspraxia caused by a mutation of the FOXP2 gene. The core phenotype of the affected KE members (aKE) is a deficiency in repeating words, especially complex non-words, and in coordinating oromotor sequences generally. Execution of oromotor sequences and repetition of phonological sequences both require WM, but to date the aKE's memory ability in this domain has not been examined in detail. To do so we used a test series based on the Baddeley and Hitch WM model, which posits that the central executive (CE), important for planning and manipulating information, works in conjunction with two modality-specific components: The phonological loop (PL), specialized for processing speech-based information; and the visuospatial sketchpad (VSSP), dedicated to processing visual and spatial information. We compared WM performance related to CE, PL, and VSSP function in five aKE and 15 healthy controls (including three unaffected members of the KE family who do not have the FOXP2 mutation). The aKE scored significantly below this control group on the PL component, but not on the VSSP or CE components. Further, the aKE were impaired relative to the controls not only in motor (i.e. articulatory) output but also on the recognition-based PL subtest (word-list matching), which does not require speech production. These results suggest that the aKE's impaired phonological WM may be due to a defect in subvocal rehearsal of speech-based material, and that this defect may be due in turn to compromised speech-based representations.
Gesehen am 15.02.2018
Article was first available online on 22 November 2017